Acupuncture Combined With Emotional Therapy of Chinese Medicine Treatment for Improving Depressive Symptoms in Elderly Patients With Alcohol Dependence During the COVID-19 Epidemic - Zhao, Fazheng; Tong, Xin; Wang, Changqing (Frontiers in Psychology, 2021)
Objective:To analyze the characteristics and psychological mechanism of depressive symptoms in elderly patients with alcohol dependence under Covid-19 epidemic and to observe the effect of acupuncture combined with emotional therapy of Chinese medicine treatment on depressive symptoms in elderly patients with alcohol dependence.Methods:60 patients were randomly divided into two groups.One group was treated by a set of emotional therapy of Chinese medicine treatment for 12 weeks(control group).One group was treated by a set of acupuncture combined with emotional therapy of Chinese medicine treatment for 12 weeks (treatment group).Comparing the curative effect between Control Group and Treatment Group;Comparing the mean alcohol consumption;Comparing the SF-36 scores before and after treatment;Comparing the scores of Hamilton Depression Scale before and after treatment of 3,6,9 weeks.Results:Based on cognitive behavior model,the characteristics and psychological mechanism of depression in elderly patients with alcohol dependence under the Covid-19 epidemic situation were summarized;The total effective rate of the control group was 60%,and that of the treatment group was 100%, p<0.05;The alcohol consumption of the patients in each group decreased significantly after treatment (p<0.05),there was no significant difference in alcohol consumption between treatment group and control group (p>0.05);After 12 weeks of treatment,there were significant differences in PF,RF,physical pain,general health status,energy and mental health between treatment group and control group (p<0.05).Before and after treatment,there were significant differences in PF,RF,physical pain,general health,energy, emotional function and mental health (p<0.05) of the teatment group.The PF, energy and mental health of the control group were significantly different before and after treatment (p<0.05);There was no significant difference between the treatment group and the control group in the scores of Hamilton Depression Scale before treatment;There was significant difference between the treatment group and the control group in the scores of Hamilton Depression Scale at 3,6 and 9 weeks after treatment.Conclusion:Attention, cognition, emotion, behavior, and physical response reinforce each other, creating a vicious cycle that reinforces and sustains the depressive symptoms of elderly alcohol dependence under Covid-19 epidemic and acupuncture combined with emotional therapy of Chinese medicine treatment for improving the depressive symptoms of elderly alcohol dependence during the epidemic period of Covid-19 has a brilliant therapeutic effect.